ANALISIS TENTANG PERILAKU HIPERAKTIF PADA PESERTA DIDIK KELAS VII SMP NEGERI 5 PONTIANAK TAHUN AJARAN 2O21/2022 - Sitoresmi, Maria Aprisilla; Asrori, Muhammad; Yuline, Yuline (Universitas Tanjungpura, 2024)
Hyperactive behavior is children who show the characteristics or symptoms of lack of concentration, a lot of movement, explosive emotions, easily discouraged and discouraged which will result in children not having friends. The purpose of this study was to describe the hyperactive behavior of class VII students of SMP Negeri 5 Pontianak. The method used in this research is descriptive quantitative method. Data was taken using indirect communication techniques, namely closed questionnaires which were distributed directly. The results showed that hyperactive behavior in class VII students of SMP Negeri 5 Pontianak was low with a percentage of 45.30%. It can be concluded that the characteristics, factors that cause it, and the impact of this behavior are in the low category with percentages of 41.67%, 48.63%, and 41.85%. Because hyperactive behavior is low, the efforts of Guidance and Counseling teachers are also lacking in dealing with this behavior. This writer shows that hyperactive behavior in class VII students of SMP Negeri 5 Pontianak is still low and does not need special handling.